Implementation of a Sentinel-2 Based Exploratory Workflow for the Estimation of Above Ground Biomass - Molisse, Giulia (2022)
Molisse, G., Emin, D., & Costa, H. (2022). Implementation of a Sentinel-2 Based Exploratory Workflow for the Estimation of Above Ground Biomass. In 2022 IEEE Mediterranean and Middle-East Geoscience and Remote Sensing Symposium, M2GARSS 2022 - Proceedings (pp. 74-77). Institute of Electrical and Electronics Engineers Inc.. https://doi.org/10.1109/M2GARSS52314.2022.9839897 ----Funding Information: This study was carried out in the framework of the MAIL project, which was funded by the European Union’s Horizon 2020 research and innovation program under the Marie Skłodowska-Curie grant agreement No 823805.